Policy on Sentencing Criminal Actors in Accordance with Pancasila Justice (Study of Decision Number: 504/Pid.B/2024/PN.Ptk) - Tama, Supra Endra; Sulchan, Achmad (UNISSULA Semarang, 2025)
Abstract. The enforcement of criminal law in Indonesia not only aims to deter offenders but is also expected to reflect the values of social justice as enshrined in the fifth principle of Pancasila. One of the major challenges in the criminal justice system is to realize a fair and proportional sentencing policy, not only towards the perpetrators but also by considering the interests of the victims and society as a whole. This research aims to analyze sentencing policies for theft offenders that embody social justice, using Case Decision Number 504/Pid.B/2024/PN.Ptk as a case study, and to evaluate the extent to which the imposed criminal sanctions reflect the principles of Pancasila justice. The research method used is a normative juridical and sociological juridical approach. Primary data were obtained from official copies of court decisions, while secondary data were obtained through literature review of criminal law literature, doctrines, and relevant regulations. The analysis was conducted qualitatively, emphasizing the legal construction built in the judge's considerations and the values of social justice within the context of Pancasila. The research results show that the sentencing policy reflected in Decision Number 504/Pid.B/2024/PN.Ptk is still dominated by a retributive paradigm, although there are considerations that attempt to accommodate aspects of substantive justice and the social conditions of the perpetrator. The criminal sentence imposed does not yet fully reflect a rehabilitative and restorative approach aimed at restoring the relationship between the perpetrator, the victim, and society. In the context of Pancasila justice, sentencing should not only serve as a means of retribution but also as an effort for rehabilitation and social reconciliation. Thus, this research recommends that future penal policies integrate the cultural and ideological values of the Indonesian nation, namely Pancasila-based social justice, through a more humane and responsive penal approach to the background of the offenders and their impact on society.